Influence of citalopram and environmental temperature on exercise-induced changes in BDNF - Goekint, Maaike; Roelands, Bart; Heyman, Elsa; Njemini, Rose; Meeusen, Romain (Neuroscience letters, 2011)
► Acute exercise increases serum BDNF and cortisol. ► Lower serum BDNF levels are found with acute citalopram administration. ► Circulating BDNF was higher with exercise in 30 °C, which raised core temperature. Purpose: Serum brain-derived neurotrophic factor (BDNF) is known to increase with exercise. This increase is believed to originate from the brain and it is suggested that monoamines are involved in BDNF regulation. Heat exposure could influence the supposed BDNF output from the brain. Therefore, we hypothesized that administration of a selective serotonin reuptake inhibitor could influence the exercise-induced increase in BDNF, and that peripheral BDNF will be higher when exercise is performed in the heat. Methods: Eleven well-trained males performed 4 experimental trials on a cycle ergometer with citalopram or placebo treatment (20 mg in 12 h) in an environmental temperature of 18 °C or 30 °C. Blood samples (BDNF and cortisol) were taken at 4 time points: at rest, after 60 min at 55% W max, after a time trial of 30 min at 75% W max and following 15 min of recovery. Heart rate and core temperature were measured. Results: Performance on the time trial was 20% worse in 30 °C compared to 18 °C ( p < 0.01), without influence of citalopram. Serum BDNF was found to be lower under citalopram treatment, while basal cortisol levels were increased ( p < 0.05). Exercise triggered an increase in both BDNF and cortisol ( p < 0.001). BDNF followed the same pattern as core temperature during exercise, with higher levels of both variables in 30 °C. Cortisol was also increased in 30 °C compared to temperate conditions ( p < 0.01). Conclusion: Exercise caused a rise in serum BDNF and cortisol. This increase was enhanced with exercise in the heat. Since permeability of the blood–brain barrier increases with exercise in the heat, the hypothesis was raised that this causes a higher cerebral output of BDNF. Serotonergic stimulation did not increase peripheral BDNF, which was even lower with citalopram administration. Future research should focus on mechanisms behind BDNF increase with exercise.